Implementasi Alat dan Mesin Pertanian dalam Mendukung Kedaulatan Pangan Indonesia - Fatmawaty, A. St; Bijaksana, A Arif (JNSTA ADPERTISI JOURNAL, 2023)
Indonesia is preparing to face three global crises, namely the food, energy and financial crises simultaneously. The world is heading for the Covid-19 Endemic which has an impact on inflation. Food sovereignty is the implementation of agricultural tools and machines in Indonesia. Therefore, this study aims to describe the choice of implementation tools and modern agricultural machinery that can be used in Indonesia. This study uses a literature study research method. At this time, the implementation of agricultural tools and machinery is an important component for modern agriculture in achieving the target of sustainable food self-sufficiency. Even technological advances in the implementation of agricultural tools and machinery will make agriculture victorious, so that Indonesia can become a world food barn. , Indonesia must also be able to independently produce its own machines.. Even further, it can become a producer and export its agricultural machinery abroad as well as being a solution to the global crisis and the current endemic Covid-19, so that it is required to pay more attention to environmental problems..In the future , there are still many obstacles that must be faced, bearing in mind that the production of weapons, especially rice, in the future will face several problems such as limited arable land, air, and manpower.